HUBUNGAN ANTARA PENDIDIKAN DENGAN PERSEPSI WISATAWAN PANTAI NIRWANA KELURAHAN SULAA KECAMATAN BETOAMBARI KOTA BAUBAU - Wa Ode Anggriyani; Baru Sadarun; Akhmad Mansyur (Jurnal Sosial Ekonomi Perikanan, 2022)
This study aims to determine the relationship between education and touris tperceptions. The location for the researchis Nirwana Beach, Sulaa Village, Betoambari District, Baubau City in September-October 2020. The method used is accidental sampling and scoring. Data were collected using questionnaires, observation, and documentation. The data analysis used is descriptive and correlation coefficient analysis. As a result, it was found that the perception of tourists on Nirwana Beach wasrated in a fairly good category and the relationship between education and tourist perceptionson Nirwana Beach was 0.941, indicating a very strong relationship because the value is closeto one.Keywords :Correlation, Education, Perception of Tourist